The Value of Collusion with Endogenous Capacity and Demand Uncertainty - Paha, Johannes (Journal of Industrial Economics, 2017)
Collusion has often been alleged in industries where long-lived capacity investments are important. This article develops a computational duopoly model with capacity investments, demand shocks and either competitive or collusive pricing. It shows that allowing for endogenous capacity investments can sometimes make collusion less valuable than competition and that it can change the normal relationships between the profitability of collusion and both the discount rate and industry-wide demand shocks.
CRIS-Team Scopus Importer:2022-11-17